Subgrade engineering characteristics of basaltic residual soil in Leizhou Peninsula, southern China - Xie, Zhenxiang; Tang, Liansheng; He, Yuan; Zhong, Qilin; Yang, Fangjian (Frontiers in Earth Science, 2023)
A 24 km urban expressway on the Leizhou Peninsula in southern China required the extensive use of different graduation basaltic residual soils nearby as subgrade filler. In order to fully understand the engineering properties of these Leizhou basaltic residual soils, four different fine granule contents (with 24.26%,55.72%,84.50%, and 94.92%) along the expressway construction sites were selected for preliminary analysis of their chemical composition, oxide content, and microstructure. Five cement contents (1.5%, 3%, 4.5%, 6%, 9%) were used to improve the residual soils based on the results of the unconfined compressive strength test and consolidated undrained triaxial compression test, the cement improvement index, which can both meet the strength requirement of the roadbed and avoid the brittle failure of soil is determined. The relationship between carrying capacity and moisture content of soil samples after outdoor improvement is studied, and explains why the moisture content corresponding to the maximum CBR of outdoor improved basalt residual soil is higher than the optimal moisture content of indoor improvement test.The relationship between the Leizhou peninsula basaltic residual soils with different granule sizes, recommended water content ratio, rolling cycle times, and compaction degree are studied outdoors, and the application suggestion of different granule sizes of basaltic residual soils in different grade highway subgrade engineering is put forward. The results are as follows: 1) The content of fine granules greatly influences the physical and mechanical properties of Leizhou peninsula basalt residual soil. 2) Due to the special colloidal state, the cement uniformity error of basalt residual soils with fine granule content of more than 85% are plus or minus 3% when it is mechanically modified, and the improvement recommended content of cement is 6% if it needs as subgrade filling materials after disturbance. 3) It is recommended that the soil moisture content before improvement in high-temperature areas should be Opt+2%, and the cement improvement time should be controlled within 50 minutes. 4) After rolling seven times, the maximum compaction degree of residual soil with fine granule content greater than 85% is less than 95%; it is only suitable for filling embankment structures below the roadbed of highway.